Basic concepts and reasons behind the emergence of religious terror activities in Indonesia: An inside view. Issue 2 (3rd January 2013) - Putra, Idhamsyah Eka; Sukabdi, Zora A.
Abstract : This study aims to understand the fundamental concepts and reasons behind the emergence of religious terror activities in Indonesia, providing an 'insider' rather than an 'outsider' view. Data were collected from a total of 40 religious terror activists in Indonesia using a set of focused group discussions and interviews. The reasons they provided for their terror activities were as follows: (1) Indonesia is seen as being in a state of war (thus justifying a defensive attack); (2) Suicide bombing is believed to be noble; (3) The West (as a whole) is targeted as it is considered the invader of Muslim countries and a representative of evil; the Indonesian government is viewed as its corrupt ally.